Does social climate influence positive eWOM? A study of heavy-users of online communities - Carla Ruiz Mafe; J. Enrique Bigné Alca\~niz; Silvia Sanz Blas; Jose Tronch (BRQ Business Research Quarterly, 2018)
This paper provides a deeper understanding of the role of social influences on positive eWOM behaviour (PeWOM) of heavy-users of online communities. Drawing on Social Interaction Utility Framework, Group Marketing and Social Learning Theories, we develop and test a research model integrating the interactions between the social climate of a website and Interpersonal Influences in PeWOM. 262 Spanish heavy-users of online communities were selected and the data analysed using partial least squares equation modelling. Overall, the model explains 59% of the variance of PeWOM on online communities. Findings reveal that interaction with other members of the online community (Social Presence) is the main predictor of PeWOM. Social Identity is a mediator between Social Presence and PeWOM. Interpersonal Influence has an important role as a moderator variable; the greater the impact of Interpersonal Influence, the stronger the relationship between Social Presence and PeWOM."
Keywords: 650; Social Identity; Social Presence; Interpersonal Influence; Word of mouth; Online reviews